Azione penale e durata dei procedimenti in Italia e in Europa: alcune osservazioni “dati alla mano” - Pascucci, Nicola (Cultura giuridica e diritto vivente, 2019)
[Prosecution and length of criminal proceedings in Italy and in Europe: some remarks supported by data]The Author considers two topical subjects: the principle of mandatory prosecution and the reasonable length of proceedings, also in a compared perspective with other European countries. The research uses, in an analytical way, data from institutional sources, to understand the practical efficacy of the current regulations about the length of criminal proceedings. The Author studies the relation between reasonable length and statute of limitations and he criticizes the recent reforms about this legal institution, also in the light of the available statistics. Finally he remarks that the reasonable length is subsidiary in comparison with other constitutional values of the fair trial.